ANALISIS KEBIJAKAN PERATURAN DAERAH KABUPATEN MALANG TERHADAP PENGELOLAAN TANAH BENGKOK DESA - Savitri, Miya (Jurnal Panorama Hukum, 2016)
Bengkok land / soil is a wealth of village assets belonging to the village in the form of certified land in the name of the village government. (Article 76 paragraph 4 of Law No. 6 of 2014 About the Village). This research use norm-legal-research used to assess policy analysis on regulations related. According to Regulation No. 4 of 2007, there were protection about the existence of a bengkok land where the wealth of the village in the form of village land are not allowed to do the release of proprietary rights to another party, except as necessary for the public interest. Release of rural land ownership rights or the so-called bengkok land determined in advance by the village chief's decision after approval by the BPD and obtain written permission from the Regent / Mayor and Governor. Regulation of land bengkok former Regent published in Regulation No. 14 Year 2015 on Guidelines for Land Management Ex Bengkok village where the proceeds from the land management bengkok former village deposited into local cash returned to each village and to support local government programs.